(untitled) (Publicaciones en Ciencias y Tecnología, 2020)
In this work we studied the influence of storage conditions and the addition of sugar in the degradation of vitamin C present in fresh juices of passion fruit, pitahaya, lemon and currant. Samples were stored at 8 and 28ºC with and without sugar for eigh hours, to monitor the variation in the concentration of vitamin C present. For both temperatures, the juices of passion fruit and pitahaya were adjusted to zero-order kinetics with sugar and first order without sugar, while lemon and redcurrant juices responded to a first order kinetics for all conditions of study. The reaction rate increased in the samples that did not contain sugar and whose storage temperature was 28 ° C. The average half- life time was 4.14 hours and the percentage of loss of vitamin C was between 40 and 80%, being the pitahaya presenting the highest concentration over time. It is concluded that storage conditions influence the degradation of vitamin C present in fresh citrus juices.